The Arbuscular Mycorrhizal Fungi’s diversity in Fabaceous trees species of Northeastern Thailand - PENPITCHA CHOOSA-NGA; UTHAIWAN SANGWANIT; THARNRAT KAEWGRAJANG (Society for Indonesian Biodiversity, 2019)
Choosa-Nga P, Sangwanit U, Kaewgrajang T. 2019. The Arbuscular Mycorrhizal Fungi’s diversity in Fabaceous trees species of Northeastern Thailand. Biodiversitas 20: 405-412. The species diversity of arbuscular mycorrhizal (AM) fungi, found in three Fabaceous tree species, namely, Dalbergia cochinchinensis, Pterocarpus macrocarpus and Xylia xylocarpa, was studied. Sixty rhizosphere soil samples were collected from the tree species plantations, and AM fungal spores were extracted and identified using their morphological characteristics. The spore density and species diversity of the fungi associated with these Fabaceous tree species was assessed. The 11 AM fungi morphospecies identified were Acaulospora (3 species), Glomus (6 species), Sclerocystis (1 species) and Scutellospora (1 species). Meanwhile, three species remained unidentified, which Unknown sp.2 was frequently found in all the three of plantations. The Shannon-Weiner diversity index of the fungal species ranged from 1.40 to 1.88, while the Evenness index ranged from 0.58 to 0.76. The diversity and Evenness index was the highest in the D. cochinchinensis plantation and lowest in the X. xylocarpa plantation. These differences may be due to differences in soil characteristics, including moisture, % organic matter, and nutrient composition. The species composition of AM fungi in the P. macrocarpus plantation was not similar with the D. cochinchinensis and X. xylocarpa plantations. It was indicated that different plant species were hosts to different AM fungal communities. Therefore, further studies are required to select the appropriate AM fungal species which have a positive effect on the growth of the three Fabaceous species when we would like to do the inoculating programs.